Food Search Strategy Changes in Caenorhabditis elegans under Chronic Starvation Conditions. Issue 7 (21st July 2016) - Urushihata, Takuya; Takuwa, Hiroyuki; Nishino, Asuka; Kikuchi, Aki; Ichijo, Akiyoshi; Obara, Chie; Wakabayashi, Tokumitsu; Sakata, Kazumi; Matsuura, Tetsuya
ABSTRACT: Starvation is a primary threat to survival in nature. This study investigated the effects of starvation on animal behavior and neural function using a nematode model. Nematodes exhibit chemotactic responses to various compounds, including diacetyl produced by food bacteria. Locomotion, chemotactic behavior, and olfactory adaptation were measured following chronic starvation. Our results revealed a starvation‐dependent reduction in locomotor activity. Chemotaxis response to the odorant diacetyl was attenuated after 2–38 hr of starvation. However, chemotactic behavior increased significantly after 48 hr of starvation compared with that after 38 hr of starvation, suggesting that food search behavior was enhanced after 48 hr of starvation. Inhibition of diacetyl adaptation was observed in the nematodes after 48 hr of starvation. However, exogenous exposure to serotonin during 48 hr of starvation caused the inhibition of diacetyl adaptation to be attenuated in following 24 hr period of normal feeding.Therefore, the inhibitory effects of starvation on olfactory adaptation may reduce chemotaxis response to the odorant diacetyl in a manner mediated by serotonin.